Comparison of Hemospray® and Endoclot™ for the treatment of gastrointestinal bleeding - Vitali, Francesco; Naegel, Andreas; Atreya, Raja; Zopf, Steffen; Neufert, Clemens; Neurath, Markus; Rath, Timo; Siebler, Jürgen (World Journal of Gastroenterology, 2019)
BACKGROUND Gastrointestinal (GI) bleeding is a common indication for endoscopy. For refractory cases, hemostatic powders (HP) represent “touch-free” agents. AIM To analyze short term (ST-within 72 h-) and long-term (LT-within 30 d-) success for achieving hemostasis with HP and to directly compare the two agents Hemospray (HS) and Endoclot (EC). METHODS HP was applied in 154 consecutive patients (mean age 67 years) with GI bleeding. Patients were followed up for 1 mo (mean follow-up: 3.2 mo). RESULTS Majority of applications were in upper GI tract (89%) with following bleeding sources: peptic ulcer disease (35%), esophageal varices (7%), tumor bleeding (11.7%), reflux esophagitis (8.7%), diffuse bleeding and erosions (15.3%). Overall ST success was achieved in 125 patients (81%) and LT success in 81 patients (67%). Re-bleeding occurred in 27% of all patients. In 72 patients (47%), HP was applied as a salvage hemostatic therapy, here ST and LT success were 81% and 64%, with re-bleeding in 32%. As a primary hemostatic therapy, ST and LT success were 82% and 69%, with re-bleeding occurring in 22%. HS was more frequently applied for upper GI bleeding (P = 0.04) CONCLUSION Both HP allow for effective hemostasis with no differences in ST, LT success and re-bleeding.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Endoclot; Gastrointestinal bleeding; Haemostasis; Hemospray; Hemostatic powder